Potential for Improvement of Student's English Language with the C4.5 Algorithm - Cyntia Lasmi Andesti; Fitria Lonanda; Nur Azizah (Indonesian Journal of Artificial Intelligence and Data Mining, 2022)
Proficiency in English is not a barrier for the Millennial Generation today. Sophisticated technology can also help increase proficiency in English. However, there are still many who do not use this technology to support English proficiency. Apart from not using technology, the millennial generation is also lacking in practicing English in everyday life. There are several factors that can predict the potential for increasing proficiency in English, namely Reading (C1), Practice (C2), Pronunciation (C3), Environment (C4), Technology (C5), English Club (C6), and Listening (C7). These factors become parameters in solving problems that occur. These parameters are used in the Data Mining method, namely Classification C4.5 or what is often called the C4.5 Algorithm. This study aims to determine the potential for increasing proficiency in English. The data processed in this study were 90 respondents from the results of the questionnaire data distributed. The software used in the processing is WEKA 3.8.6 Software. The processing steps are to calculate the Entropy value and Gain value of each attribute, form the root node (node) based on the highest gain value and form a decision tree. The results of the discussion on the Weka 3.8.6 software, the data accuracy rate is 90 % or 81 data and the error rate is around 10 % or 9 Data. From the data of 90 respondents, the factors that influence the potential for increasing proficiency in English are Practice (C2).